Infantile dermatofibroma. - Milano, A. (European Journal of Pediatric Dermatology, 2010)
Case report. A 6-year-old boy presented with a 7-month history of an initially 2 mm in size cutaneous lesion on his chest, which tripled its volume in the subsequent months. Physical examination revealed on the lateral region of the right hemithorax a 6 mm wide (Fig. 1) and 3 mm thick nodule, brownish, sharply demarcated, of hard-elastic consistency, adherent to the skin, mobile on the deep tissues and painless. The dermoscopic examination showed a white plaque with rare central telangiectasias (Fig. 2). The nodule was excised under local anesthesia. The histological examination (Fig. 3 and inset) showed slightly thickened epidermis and in the dermis a tumor mainly consisting of collagen bundles with storiform aspect and fibrocytes, leading to final diagnosis of dermatofibroma.